PENGEMBANGAN E-LKPD KIMIA BERBASIS ICARE UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PADA MATERI HIDROLISIS GARAM - Afrianti, Yolanda; Rina Elvia; Solikhin, Febrian (ALOTROP, 2025)
This research is a  research and development of ICARE-based chemical learning e-worksheet which aims to determine the feasibility of learning e-worksheet, student responses, students' scientific process skills based on observation and improvement of science process skills after using ICARE-based chemical learning e-worksheet. The development model used was ADDIE. The research was conducted at SMA Negeri 7 Bengkulu City with the research subjects being 12 students of class XI MIPA 5 for the small group trial, and 36 students of class XI MIPA 4 for the large group trial. The instruments in this study were interview sheets, student need questionnaires, validation sheets, student response questionnaires, observation sheets, and tests. From the results of the study, it was found that (1) ICARE-based chemical learning e-worksheet was categorized very feasible by media and materials experts with a percentage of media and material aspects of 93.89% and material of 89.76%, (2) student responses to chemical- based learning e-worksheet. ICARE is in the very good category with an average percentage of 89.90%, (3) students' science process skills based on observation get an average percentage of 82.84% in a good category, and (4) after using ICARE-based chemical learning e-worksheet on salt hydrolysis materials showed an increase in six indicators of science process skills as measured by an average N-gain score of 0.65 on the moderate criteria. Keywords: Learning e-worksheet; ICARE; Science Process Skills; Salt Hydrolysis Materials